The Boy who ate stars - Yuson, Alfred (Pasig, Metro Manila : Cacho Publishing House, Inc, 1991)
The boy had always wanted to eat stars. At night, he woulf look up at the little areas of the sky , and wish so hard that he may reach out beyond the trees to pluck the twinkling stars, and put them into his mouth.
Keywords: Stars-Fiction